Prognostic significance of the Bethesda cytological classification in recurrent thyroid carcinoma - I. M. Zakharova; O. G. Grigoruk; S. A. Terekhova; D. I. Ganov; A. F. Lazarev; I. V. Vikhlyanov; Yu. A. Antonova; E. K. Semeryanova (Опухоли головы и шеи)
Introduction. The Bethesda System for Reporting Thyroid Cytopathology allows to standardize interpretation of fine needle aspiration biopsy of thyroid nodules with assessment of suspected malignancy risk. Analysis of prognostic significance of cytological data, using the Bethesda System as an example, is necessary for determination of tumor process aggressiveness and possibility of development of recurrences.Aim. To study prognostic significance of the Bethesda System for Reporting Thyroid Cytopathology in recurrent thyroid carcinoma.Materials and methods. Results of examinations and surgical interventions performed at the Altai Regional Oncological Dispensary (Barnaul) during a 3-year period in 503 patients (423 women (84.1 %) and 80 (15.9 %) men) with thyroid carcinoma are analyzed. In 440 patients, thyroid carcinoma in surgical material was found for the first time (R0 – primary patients); in 63 patients, disease recurrence was diagnosed (R1 – presence of recurrence). At the time of surgery, median patient age was 51 years (interquartile range 40–62 years). The inclusion criterion for the study was morphologically confirmed diagnosis of thyroid carcinoma; the exclusion criterion was the absence of cytological examination per the Bethesda System in patients with recurrent carcinoma. Data from medical records, disease histories and cancer registry were evaluated taking into account clinical and anamnestic characteristics of a special classifier for determination of risk factors of disease recurrence. Data processing was performed using Microsoft Excel software. At the preoperative stage, in primary patients, results of ultrasound and cytological examination of the fine needle aspiration biopsy of thyroid nodules were analyzed. Results of cytological examination per the Bethesda System were considered as an independent risk factor of recurrence. Orange Data Mining (version 3.3.37.0) and RStudio (version 4.3.1) software were used for data analysis. Distributions of quantitative variables were evaluated using the Kolmogorov–Smirnov and Shapiro–Wilk tests. Normal distribution hypothesis was rejected at p <0.20 for Kolmogorov–Smirnov test and at p <0.05 for Shapiro–Wilk test.Results. According to the data, median time to recurrence was 2 years (Q1–Q3 – 1–6 years), minimal time to its development was 1 year, maximal – 20 years. 1-year recurrence-free survival was 100 %, 3-year was 91 %, 5-year was 86 %, 10-year was 59 %, 15-year was 25 %. Mean time to recurrence in 50 % of patients was 9.8 ± 0.9 years. Risk of recurrence of thyroid carcinoma of category IV per the Bethesda System was 3.623 times (72.4 %) lower compared to category III (hazard ratio 0.276; 95 % confidence interval 0.110–0.691; p = 0.006). Recurrence-free survival in patients with thyroid carcinoma of category VI per the Bethesda System was significantly higher (р = 0003 and p < 0.001) than in patients with category III and IV cytopathology.Conclusion. Cytological conclusion of category III per the Bethesda System is 2.755 times more common in recurrence group than of category VI. Category VI cytopathology, 88.7 % of which are papillary thyroid carcinoma with conclusive cell signs, is characterized by relatively low risk of recurrence. Cytologic conclusion of categories III and IV per the Bethesda System is an unfavorable prognostic factor in preoperative diagnostics due to undetermined interpretation of the pathology. These categories are commonly observed in patients with more aggressive disease progression.